PENGARUH MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP BUDAYA KERJA GURU DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SD NEGERI 1 MULYOHARJO - Annisa Edna Nur Fitriani; Nur Rohman (Jurnal Manajemen Pendidikan, 2026)
The current reality of education in Indonesia shows that the leadership of school principals is often more administrative than inspirational, causing teachers' work culture to tend to be monotonous and less adaptive to the demands of the Independent Curriculum. This study aims to analyze the influence of principal leadership on teacher work culture in improving the quality of learning at SD Negeri 1 Mulyoharjo, Jepara Regency. A correlational quantitative approach was used with a sample of 10 active teachers through a 5-point Likert scale questionnaire (20 items: 10 for variable X, 10 for Y). Data analysis included descriptive statistics, Pearson Product Moment correlation test, and simple linear regression. The results show that the average principal leadership score is 4.32 (high category) and the teacher work culture score is 4.65 (very high), but there is a weak negative correlation (rxy = -0.4097; p=0.2397>0.05) with an influence of 16.8% (R²=0.168; Y=71.60-0.581X). The novelty of this study lies in the finding that in schools with a mature work culture, leadership acts as a situational facilitator (Fiedler's contingency theory, 1967), not a major determinant, in contrast to Burns' transformational theory (1978), which dominates Indonesian literature. Implications: Principals need to adopt the Hersey-Blanchard delegative style for professional teachers.